2014
DOI: 10.1093/mnras/stu052
|View full text |Cite
|
Sign up to set email alerts
|

The formation and evolution of small star clusters

Abstract: Recent observations show that small, young, stellar groupings of ∼ 10 to 40 members tend of have a centrally-located most massive member, reminiscent of mass segregation seen in large clustered systems. Here, we analyze hydrodynamic simulations which form small clusters and analyze their properties in a manner identical to the observations. We find that the simulated clusters possess similar properties to the observed clusters, including a tendency to exhibit mass segregation. In the simulations, the central l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 61 publications
1
53
0
Order By: Relevance
“…Numerical simulations have varied predictions on whether or not there is primordial mass segregation in clusters. Some simulations find mass segregation of stars/sink cells in clusters from very early times (e.g., Maschberger & Clarke 2011;Girichidis et al 2012;Kirk et al 2014;Myers et al 2014). Other simulators find no evidence of mass segregation (e.g., Parker et al 2014), while find that evidence for or against mass segregation depends on the method used to measure it.…”
Section: Discussionmentioning
confidence: 99%
“…Numerical simulations have varied predictions on whether or not there is primordial mass segregation in clusters. Some simulations find mass segregation of stars/sink cells in clusters from very early times (e.g., Maschberger & Clarke 2011;Girichidis et al 2012;Kirk et al 2014;Myers et al 2014). Other simulators find no evidence of mass segregation (e.g., Parker et al 2014), while find that evidence for or against mass segregation depends on the method used to measure it.…”
Section: Discussionmentioning
confidence: 99%
“…The presence (or absence) of such massive stars can affect the stellar content and overall evolution of low-mass clusters (Pelupessy & Portegies Zwart 2012). As voracious consumers of star-forming material, the most massive stars may form early-on (Kirk et al 2014), thereby increasing the likelihood that they will affect the gas content of a star-forming region before large numbers of lower mass stars have formed.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…In contrast, NGC 2023/NGC 2024 displays high levels of mass segregation for the four most massive cores, with the 10-20 most massive cores also mass segregated to a high level. Kirk et al (2016b) find that all three regions in Orion B are mass segregated, according to the group segregation method developed by Kirk & Myers (2011) and Kirk et al (2014). This method is very different to conventional methods of defining mass segregation, such as quantifying the change in the IMF as a function of distance from the centre of a star-forming region.…”
Section: Comparison With Previous Workmentioning
confidence: 99%
“…Kirk et al (2016b) found that none of the three subregions are spatially substructured according the Q-parameter (Cartwright & Whitworth 2004;Cartwright 2009), which is surprising as all three regions appear visually substructured. The authors also claim to find mass segregation of the cores, but using the group segregation ratio method (Kirk & Myers 2011;Kirk, Offner & Redmond 2014). However, Parker & Goodwin (2015) find serious flaws in this technique, to the extent that it may not accurately find or quantify mass segregation in spatially substructured star-forming regions.…”
Section: Introductionmentioning
confidence: 99%